Pengaruh Kinerja Pegawai, Motivasi Kerja, Komunikasi dan Budaya Kerja terhadap Pelayanan Kepegawaian (Studi Kasus pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Denpasar) - I Made Karang Wira Wicaksana; A.A. Ayu Dewi Larantika; I Gede Agus Wibawa (Public Inspiration : Jurnal Administrasi Publik, 2024)
The aim of this research is to understand and analyze the influence of employee performance, work motivation, communication and work culture on personnel services at the Denpasar City Personnel and Human Resources Development Agency. This research uses a quantitative approach with primary and secondary data types. The total population in this study was 1,996 employees, and the number of samples obtained using the Slovin formula calculation was 333 respondents. The data analysis technique used is multiple linear regression with the SPSS application. The test results prove that partially and simultaneously employee performance, work motivation, work communication and work culture have a positive and significant effect on the quality of personnel services at the Denpasar City Personnel and Human Resources Development Agency. The value of the coefficient of determination or Adjusted R square shows a value of 0.862, from these results it means that all independent variables (employee performance, work motivation, work communication and work culture) have a contribution of 86.2% to the dependent variable (performance) with a very strong level of determination. and the remaining 13.8% is influenced by other factors outside this research.